PENGARUH ECONOMIC VALUE ADDED TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERCATAT DI BURSA EFEK INDONESIA - lrawan, Ronny (Jurnal Akuntansi Kontemporer, 2010)
The goal of every companies is to maximize their value. Value of them is correlated with the performance that achieved. Companies value is measured with stock return or stock price. If the peiformance is increase, so their value will increase also. Companies performance usually are measured by one of traditional accounting measurement such as accounting profit, revenue growth, return on investment. Traditional measurements were supposed having more risk, because if companies only focus on the big growth without consider about the higher return than cost of capital, it will destroy company value. One alternative of performance measurements that can be used is economic value added. This research analyzed the influenced of economic value added to stock return, using alternative models. Based on linier regression testing, (his study found that there was no a significant effect of current or previous economic value added to current stock return. Second, there was no a significant effect of the change of current or previous economic value added to the change of current stock return of the public companies listed on Indonesian Stock Exchange in 2002 until 2007.